Trends of Poisoning in Western Utter Pradesh A Clinico-pathological Study - Patel, N S; Srivastava, A K; Kumar, Amit; Kumar, J V Kiran; Nandwani , S (Journal of Indian Academy of Forensic Medicine, 2014)
Drugs and chemicals are a great danger to human lives but most of the poisoning in our country  is due to pesticides and insecticides. In this paper the cases of poisoning admitted in Subharti Hospital  Meerut were studied for epidemiological, clinico-pathological and medico-legal aspects. Majority of the  poisoning victims are young adults, Hindus between 16-35 years of age with preponderance of Male  (61.11%) over female (38.88%). Most of the victims belonged to lower or lower-middle class. Pesticides  especially Aluminium phosphide (31.74%) and organophosphates (20.63%) are responsible for more than  two-third (72.22%) of the casualties. Nausea & vomiting was the most common symptom seen in 41.26%  patients followed by altered consciousness (39.68%) and burning pain in abdomen (21.42%). Majority of  poisoning cases (82.53%) were suggestive of suicide, of which family quarrel (36.54%) and  unemployment or loss in business (14.42%) were more common in male and ill treatment by husband/in laws (13.46%) in female.
Keywords: Poison; Pesticide & insecticide; Nausea & vomiting; Constricted pupil; Suicidal